Molecular characterization of ST15 carbapenem-resistant Klebsiella pneumoniae isolated in a single patient - Yongjin Hu; Rong Tang; Shanshan Jin; Jiahao Guan; Xiaoxiao Meng; Zengpeijie Dan; Ruilan Wang; Hong-Yu Ou; Jian Lu (Journal of Global Antimicrobial Resistance)
Background: The carbapenem-resistant Klebsiella pneumoniae (CRKP) poses a serious threat to antibiotic applicability and public health. During treatment, K. pneumoniae (KP) frequently exhibits shifts in drug-resistant phenotypes, complicating clinical treatment as it transitions from sensitivity to resistance. In this study, we analysed the clinical and molecular characteristics of drug resistance changes in KP strains isolated from a single patient, and the potential mechanisms underlying these resistance changes. Methods: Antimicrobial susceptibility test and string test were conducted to evaluate the resistant and virulent characterization of the strains. Pulsed-field gel electrophoresis (PFGE) was used to investigate the homology relationship between the strains. The whole genome sequencing and phylogenetic analysis of 9 representative isolates was also performed. The transfer ability of the drug-resistant plasmid was studied by plasmid conjugation experiment. The transconjugants were verified by polymerase chain reaction amplification of specific genes, antimicrobial susceptibility test and PFGE. Results: Our results revealed that 9 KP strains, isolated from the same patient, exhibited ‘resistance-sensitivity-resistance-sensitivity’ alternately to carbapenems. The differences in DNA fingerprint bands among the nine KP isolates were ≤3, which can be classified as the same PFGE type. Phylogenetic analysis showed that these 9 strains constituted a distinct branch within the phylogenetic tree. All nine KP strains belonged to the ST15-KL19 clone. Six of the strains were classified as CRKP, all of which carried 11 drug resistance genes: oqxB, oqxA, fosA6, aac(3)-lld, blaSHV-28, blaKPC-2, blaOXA-1, mph(A), tet(A), catB3 and aac(6′)-lb-cr, mediating drug resistance to quinolones, fosfomycin, aminoglycosides, β-lactam, carbapenems, macrolides and chloramphenicol, belonging to multi-drug resistant bacteria. The carbapenem-resistant plasmid p2-KP3762–1 was found to transfer within species, from CRKP to hypervirulent KPRJF293HA, carbapenem-sensitive KP KP3657 and Escherichia coli C600 at a frequency of (1.19 ± 1.58) ×10−6, (1.09 ± 1.38) ×10−7 and (10.9 ± 9.53) ×10−6 respectively, resulting in the dissemination of carbapenem resistance genes. Conclusions: In this study, KP strains isolated from a single patient exhibited an alternating phenotype of resistant-sensitive-resistant-sensitive to carbapenems. The 9 KP isolates share a high degree of genetic similarity. The plasmid p2-KP3762–1, harbouring the carbapenem resistance gene blaKPC-2, may undergo inter-strain and inter-clone transfer via conjugation in the patient during treatment. Furthermore, our findings suggest that the pathogens in this patient are likely to have a common ancestral origin.